Assessing Avascular Necrosis Risk and Outcomes after Open Reduction for Developmental Dysplasia of the Hip in Children in Pakistan - Shahid Husssin, Syed Abdur Rub Abidi, Aman Ullah Khan Kakar, Saeed Ahmad, Junaid Javaid, Muhammad Muneer Haider, Tauseef Raza, Asnaf Siddique (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Developmental dysplasia of the hip (DDH) is a common pediatric orthopedic condition that, if untreated, can lead to long-term disability. Open reduction is often required in late-presenting cases but carries the risk of avascular necrosis (AVN) of the femoral head. Objectives: This study aims to assess the incidence, risk factors, and outcomes of AVN in children undergoing open reduction for DDH in Pakistan. Methods: This retrospective observational study was conducted at Shahid Hussain Orthopedic and General Hospital, Timergara during December 2022 to May 2023. A total of 95 children (aged 12 months to 6 years) who underwent open reduction for DDH were included in the study. Patient demographics, surgical details, post-operative care, and follow-up data were collected. AVN incidence was determined using the Salter and Kalamchi classification, while functional outcomes were evaluated using the Modified McKay criteria. Results: AVN was identified in 24 patients (25%). Age at surgery above three years, prolonged immobilization (>8 weeks), and the medial surgical approach were associated with a higher incidence of AVN. Functional outcomes were significantly better in patients without AVN, with 95% achieving excellent or good results compared to 75% in those with AVN (p=0.01). Radiographic outcomes also showed a higher incidence of residual hip dysplasia in AVN patients, with 35% classified as Severin IV. Conclusion: It is concluded that AVN is a major complication following open reduction for DDH, with a significant impact on functional and radiographic outcomes. Early intervention, careful surgical technique selection, and optimized post-operative management can help reduce AVN risk. Keywords: Developmental dysplasia of the hip, avascular necrosis, open reduction, pediatric orthopedics, hip dysplasia, Pakistan.